2024
DOI: 10.3390/pharmaceutics16020288
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Nanostructures as Emerging Materials for Gene Delivery Applications

Sara Yazdani,
Mehrdad Mozaffarian,
Gholamreza Pazuki
et al.

Abstract: Gene therapeutics are promising for treating diseases at the genetic level, with some already validated for clinical use. Recently, nanostructures have emerged for the targeted delivery of genetic material. Nanomaterials, exhibiting advantageous properties such as a high surface-to-volume ratio, biocompatibility, facile functionalization, substantial loading capacity, and tunable physicochemical characteristics, are recognized as non-viral vectors in gene therapy applications. Despite progress, current non-vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 361 publications
0
1
0
Order By: Relevance
“…33,34 Yazdani et al found that the carbonbased nanostructure, including carbon nanotubes, carbon quantum dots, and nanodiamonds have potential application on gene delivery. 35 However, they still exhibit significant toxicity at the nanoscale. In a previous study, DWPs with a size comparable to real wear debris were known to possess a discernible degree of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Yazdani et al found that the carbonbased nanostructure, including carbon nanotubes, carbon quantum dots, and nanodiamonds have potential application on gene delivery. 35 However, they still exhibit significant toxicity at the nanoscale. In a previous study, DWPs with a size comparable to real wear debris were known to possess a discernible degree of toxicity.…”
Section: Introductionmentioning
confidence: 99%